Roanoke : the lost colony : an unsolved mystery from history - Yolen, Jane.; Stemple, Heidi E. Y. author; Roth, Roger (Roger Almon) (New York : Scholastic, 2003)
In this spine-tingling book from the nonfiction An Unsolved Mystery from History picture book series, journey to colonial America and discover the enduring mystery of the missing Roanoke Colony. In 1587 John White was chosen by Sir Walter Raleigh to lead a new colony at Roanoke off the Atlantic coast. After bringing many men, women, and children to the new land, White went back to England to gather supplies for the long winter. But when he finally returned to the fort almost three years later, he found that all of the colonists had vanished.
O
b
b
Keywords: Roanoke; Colony; North Carolina